SEDIMENT SOURCES AND THE FLOOD RECORD FROM WANGHU LAKE, IN THE MIDDLE REACHES OF THE YANGTZE RIVER - Yi C.; Liu H.; Rose N.L.; Yang H.; Ni L.; Xie P. (My University, 2006)
A sediment core was collected from the centre of Wanghu Lake, in the Middle Reaches of the Yangtze River. The recent part of the core was dated using a combination of 210Pb and spheroidal carbonaceous particle (SCP) techniques. Extrapolating this chronology dated the laminated section of the core, between 723 and 881 mm, to the first half of the 18th century and this section was selected for detailed study. The thicknesses of the laminae were measured using reflecting and polarizing microscopes whilst geochemistry was determined by an electron probe. The thickness of the dark layers was found to be positively correlated with titanium concentrations, and negatively correlated with aluminium and potassium concentrations. The thickness of the light layers was found to be negatively correlated with the concentrations of titanium. It is concluded that the dark layers were deposited from the Fushui River, a tributary of the Yangtze River, under periods of normal flow whilst the light layers were mainly deposited from the Yangtze River itself during flood periods. Documentary evidence for floods occurring in the lake catchment corresponded with thick laminations of high titanium concentration. Further, two of the three thickest, light laminations with low titanium concentrations were found to be synchronous with recorded flood dates of the main Yangtze River in its Middle Reaches, but one was synchronous with a local drought. These data suggest that the lake sediment provides an archive of the relative water levels of the Yangtze and Wanghu including floods of both the main Yangtze River and the local hydrological regime. © 2006 Elsevier B.V. All rights reserved.
Keywords: FLOOD SOURCES; LAMINATED SEDIMENTS; SEDIMENT GEOCHEMISTRY; YANGTZE RIVER